Evaluation of the Effects of Flushing Feed Manufacturing Equipment with Chemically- Treated Rice Hulls on Porcine Epidemic Diarrhea Virus Cross Contamination During Feed Manufacturing - J. T. Gebhardt; J. C. Woodworth; C. K. Jones; Phillip Charles Gauger; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; M. Muckey; R. A. Cochrane; M. Niederwerder; C. R. Stark; J. Bai; et al. (Kansas Agricultural Experiment Station Research Reports, 2016)
Various strategies have been proposed to mitigate potential risk of porcine epidemic diarrhea virus (PEDV) transmission via feed and feed ingredients. Wet decontamination has been found to be the most effective decontamination of feed mill surfaces; however, this is not practical on a commercial feed production-scale. Another potential mitigation strategy, easier to implement, would be using chemically-treated rice hulls flushed through the feed manufacturing equipment. The objective of this experiment was to determine the impact of MCFA- or formaldehyde-treated rice hull flush batches as potential PEDV mitigation strategies during feed manufacturing. Feed without evidence of PEDV RNA contamination was inoculated with PEDV. Based on PCR analysis, this feed had a Ct = 30.2 and was confirmed infective in bioassay. After manufacture of PEDV positive feed, untreated rice hulls, or rice hulls treated with Sal CURB, 2%, or 10% medium chain fatty acid blend (MCFA; 1:1:1 ratio of caproic, caprylic, and capric acid) were flushed through laboratory-scale mixers. For the untreated rice hulls, 3 of 6 samples had detectable PEDV RNA (avg. Ct = 41.4) while 1 of 6 Sal CURB treated rice hull flush samples and 2 of 6 of the 2% MCFA rice hull flush samples had detectable PEDV RNA. However, PEDV RNA was not detected in any of the 10% MCFA rice hull flush samples. Additionally, rice hulls treated with 10% MCFA were mixed and discharged through a production-scale mixer and bucket elevator following manufacturing of PEDV positive feed. In the production-scale system, no rice hull flush or feed samples from the mixer following chemically-treated rice hull flush had detectable PEDV RNA. However, one 10% MCFA rice hull sample collected from the bucket elevator discharge spout had detectable PEDV RNA. Dust collected following mixing of PEDV-contaminated feed had a large quantity of PEDV RNA (avg. Ct = 29.4). Dust collected immediately after the 10% MCFA rice hull flush batch had a reduced quantity of PEDV RNA (Ct = 33.7), and the subsequent feed following the 10% rice hull flush had no detectable PEDV RNA. Pigs inoculated with dust collected after manufacturing PEDV-positive feed were shedding PEDV RNA by 2 dpi and continued to have detectable RNA until necropsy. Dust collected from the 10% MCFA rice hull flush batch or the subsequent batch was not infective. Overall, the use of rice hull flushes effectively reduced the quantity of detectable RNA present after mixing a batch of PEDV-positive feed. Chemical treatment of rice hulls with Sal CURB and 10% MCFA provided additional reduction in detectable RNA present in the rice hull flush samples. Finally, dust collected after manufacturing PEDVinoculated feed contains a very high quantity of viral RNA and was found infective, demonstrating it has the potential to serve as a vector for PEDV transmission.
Keywords: chemical treatment; flush; medium chain fatty acid; PEDV; swine